Apa yang Melatarbelakangi Keinginan Negara untuk Memiliki Senjata Nuklir? Studi Kasus Iran dan Korea Utara - Muhammad Erza Pradana (Jurnal Sentris, 2023)
Why do states want to acquire nuclear weapons? In other words, what drives nuclear-aspiring states? This is the basic question that the author seeks to address in this research. To do so, this research will focus on two standout cases: Iran and North Korea. By employing structural realism as a tool of analysis, the author argues that it is the structure of the international system that drives both Iran and North Korea to acquire nuclear weapons of their own. Specifically, it is the highly unequal distribution of power both regionally and globally that encourages both states to go nuclear. At the global level, both Iran and North Korea found themselves in hostilities with a much more powerful state, the United States. The hostilities and the fact that the United States is way more powerful increase the fear of being attacked in both countries. Similarly, at the regional level, both states face neighbors that are relatively more powerful and have alliances with the United States. Thus, this imbalance of power and the fear it created in both Iran and North Korea give them great incentive to go nuclear, as nuclear weapons would act as a deterrent against any possible aggression. This research is qualitative and based on the literature study data collection method. Keywords: Nuclear proliferation; national security; distribution of capabilities; structural realism REFERENCES   Abulof, Uriel. 2014. "Revisiting Iran’s nuclear rationales." International Politics 51(3), 404-415. Albright, David, and Andrea Stricker. 2010. "Iran’s Nuclear Program." In The Iran Primer: Power, Politics, and US Policy, edited by Robin Wright, 77-81. Washington, D.C.: United States Institute of Peace Pres.  Bowen, W.Q., and J. Brewer. 2011. "Iran’s nuclear challenge: Nine years and counting." International Affairs 87(4): 923–943.  Chubin, S. 2007. "Iran: Domestic politics and nuclear choices." In Strategic Asia 2007–08: Domestic Political Change and Grand Strategy, edited by A.J. Tellis, M. Wills and N. Bisley, 301–340. Washington DC: National Bureau of Asian Research.  Cronin, Patrick M. 2008. "The Trouble with North Korea." In Double Trouble: Iran and North Korea as Challenges to International Security, edited by Patrick M. Cronin, 79-89. Wesport: Praeger Security International  Buszynski, Leszek. 2021. "North Korea's Nuclear Diplomacy." In Routledge Handbook of Contemporary North Korea, edited by Adrian Buzo, -170. Oxon: Routledge.  Donnelly, Jack. 2005. "Realism." In Theories of International Relations, edited by Scott Burchill, Andrew Linklater, Richard Devetak, Jack Donnelly, Christian Reus-Smit Matthew Paterson and Jacqui True, 29-54. Basingstoke: Palgrave Macmillan.  Greitens, Sheena Chestnut. 2020. "Proliferation of weapons of mass destruction." In The Globalization of World Politics: An Introduction to International Relations, by John Baylis, Steve Smith and Patricia Owens, 465-480. Oxford: Oxford University.  Hobbs, Christopher, and Matthew Moran. 2014. Exploring Regional Responses to a Nuclear Iran. Basingstoke: Palgrave Macmillan.  Ikenberry, G. John, Michael Mastanduno, and William C. Wohlforth. 2011. "Introduction: unipolarity, state, and systemic consequenses." In International relations theory and the consequences of unipolarity, edited by G. John Ikenberry, Michael Mastanduno and William C. Wohlforth, 1-32. Cambridge: Cambridge University Press.  Jackson, Robert, and Georg Sørensen. 2013. Introduction to International Relations: Theories and Approaches. Oxford: Oxford University Press.  Jackson, Van. 2018. On the Brink: Trump, Kim, and the Threat of Nuclear War. Cambridge: Cambridge University Press.  Jørgensen, Knud Erik. 2018. International Relations Theory: A New Introduction. London: Palgrave. Kaufman, Joyce P. 2021. A Concise History of U.S. Foreign Policy. Lanham, Maryland: Rowman & Littlefield  Krauthammer, Charles. 1990. "The Unipolar Moment." Foreign Affairs 70(1), 23-33. Mærli, Morten Bremer, and Sverre Lodgaard. 2007. "Introduction." In Nuclear Proliferation and International Security, edited by Morten Bremer Mærli and Sverre Lodgaard, 1-5. Oxon: Routledge.  Mearsheimer, John J. 2018. The Great Delusion: Liberal Dreams and International Realities. New Haven: Yale University Press.  —. 2001. The Tragedy of Great Power Politics. New York: WW Norton & Company. Mearsheimer, John J., and Stephen M. Walt. 2007. The Israel Lobby and US Foreign Policy. New York: Farrar, Straus and Giroux.  Pollack, Jonathan D. 2011. No Exit: North Korea, Nuclear Weapons and International Security. New York: Routledge.  Popoola, Michael Akin, Deborah Ebunoluwa Oluwadara, and Abiodun A. Adesegun. 2019. "North Korea Nucler Proliferation in the Context of the Realist Theory: A Review." European Journal of Social Sciences 58(1), 75-82.  Porter, Patrick. 2015. The Global Village Myth: Distance, War and the Limits of Power. Washington, D.C.: Georgetown University Press.  Sharma, Anu. 2022. Through the Looking Glass: Iran and Its Foreign Relations. New York: Routledge  Smith, Shane. 2021. "Nuclear Weapons and North Korean Foreign Policy." In Routledge Handbook of Contemporary North Korea, edited by Adrian Buzo, 141-154. Oxon: Routledge. Tagma, Halit M. E. 2020. "Realism and Iran’s Nuclear Program." In Understanding and Explaining the Iranian Nuclear 'Crisis', by Halit M. E. Tagma and Paul E. Lenze Jr., 65-103. Lanham: Lexington Books.  Tagma, Halit M.E, and Paul E. Lenze Jr. Understanding and Explaining the Iranian Nuclear 'Crisis'. Lanham: Lexington Books, 2020.  Taylor, Steven J., Robert Bogdan, and Marjorie L. DeVault. 2016. Introduction to Qualitative Research Methods: A Guidebook and Resource. New Jersey: John Wiley & Sons, Inc. Thomas, Garth. 2017. " Realism And Its Impact To The North Korean, South Korean, And Chinese Nuclear Programs (." Master's Thesis. Baltimore, Maryland: Johns Hopkins University, August. Accessed June 27, 2022. https://jscholarship.library.jhu.edu/bitstream/handle/1774.2/60434/THOMAS-THESIS 2017.pdf?sequence=1&isAllowed=y.  Viotti, Paul R., and Mark V. Kauppi. 2012. International Relations Theory. Boston: Longman. Vromen, Ariadne. 2010. "Debating Methods: Rediscovering Qualitative Approaches." In Theory and Methods in Political Science, edited by David Marsh and Gerry Stoker, 249-266. Basingstoke: Palgrave Macmillan.  Waltz, Kenneth N. 1979. Theory of International Politics. Reading: Addison-Wesley Publishing Company, Inc.  Waltz, Kenneth. 2000. "Structural Realism after the Cold War ." International Security 25(1), pp. 5– 41.  Yonhap News Agency. 2018. N. Korea will not give up nuclear weapons: Mearsheimer . March 20. Accessed May 18, 2023. https://en.yna.co.kr/view/AEN20180320010200315.